KNOWLEDGE, ATTITUDE AND PRACTICES REGARDING CRIMEAN - CONGO HAEMORRHAGIC FEVER AMONG HEALTHCARE WORKERS IN BALOCHISTAN - Sheikh, Nadeem S.; Sheikh, Azeem S.; Sheikh, Aqleem A. (Journal of Ayub Medical College Abbottabad, 2004)
Background: The objective of this study was to determine the knowledge, attitude and practices regarding Crimean-Congo Haemorrhagic Fever (CCHF) among healthcare workers at a tertiary care referral hospital in Balochistan. Methods: A cross-sectional survey was conducted in April - May 2000 among the doctors, nurses and laboratory technicians of Sandeman Provincial Teaching Hospital, Quetta, Balochistan. A questionnaire was formulated which included the demographic data of the respondents and their knowledge, attitude and practices towards CCHF. Results: A total of 235 healthcare personnel including 150(63.8%) doctors, 50(21.2%) nurses and 35(15%) laboratory technicians were interviewed during the survey. Seventy percent (164) of the subjects were males while 30% (71) were females. One fifty-five (66%) of the total respondents claimed to know what CCHF was. By designation 120 (80%) of doctors, 30 (60%) of nurses and 5 (14%) of laboratory technicians had a prior knowledge about CCHF. One twenty (80%) of the doctors knew the most common presentations of CCHF. All categories of the respondents had a poor knowledge regarding the burial procedure of dead patients. Conclusion: This study was an indicator of the poor level of knowledge of healthcare workers regarding the clinical presentations and the modes of spread of CCHF. It is the dire need of the time to educate the healthcare workers about the common preventive measures of this disease, which has resulted in the loss of several important lives in the past in this region. KEY WORDS: Viral Haemorrhagic Fever, Haemorrhagic Fever, Crimean Congo Haemorrhagic Fever.